(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Meningiomas are extracerebral, from the pia mater of the brain and spinal cord, and the choroid plexuses of the cerebral ventricles or arising ectopically in the bones of the skull, spine and along the nerve roots of the tumor. Meningiomas account for approximately one third of all intracranial tumors..